Drivers of Subjective Well-Being Under Different Economic Scenarios - Arrondo, Rubén; Cárcaba, Ana; González, Eduardo (Frontiers in Psychology, 2021)
This paper explores the evolution of the driving forces that shape individual subjective well-being (SWB) in Spain from 2013 to 2018. Several socio-demographic, material conditions and quality of life (QoL) variables are considered as potential drivers of SWB. The data come from a large survey carried in two different time periods. The first one (2013) is characterized by a negative economic scenario as a result of the global financial crisis of 2008. The second one (2018) is characterized by fast economic recovery. Our results suggest that the material conditions variables, especially unemployment, have a much deeper impact on SWB during economic downturns than during economic recovery periods. Social connections and health status are determinant factors behind SWB, especially if the economy is working well. Our results also point to changes in gender effects. While women were happier than men in 2013, this effect disappears in 2018. Paradoxically, this suggest an increase in female expectations about their own lives during this period.